Evaluation of Credit Sales and Non-Performing Loans (NPL) of PT. Bank Sulutgo Ranotana Sub-branch Office - Deissy A.Kristiani Leohang; Jenny Morasa; Sherly Pinatik (Formosa Journal of Multidisciplinary Research, 2023)
Credit is a business activity in the form of providing cash or non-cash loans to other people based on the procedures applied. PT. BSG is a BUMN engaged in community service such as providing loans to customers. In the case that occurred at PT. BSG Limboto Branch in 2015 and 2016 the loans provided turned out to be indications against the law and deviations from statutory SOPs governing the application and granting of credit. After investigation, the collateral for the credit agreement did not meet the requirements, causing credit losses which could affect cash flow at PT. BSG. Poor credit sales management can lead to losses, therefore the company is required to place more emphasis on its management system so as to minimize credit losses experienced by the company. The purpose of this study is to evaluate the management of credit sales and credit losses implemented by PT. BSG KCP Ranotana based on the method and type of qualitative descriptive research. The results showed that the management of credit sales by PT. BSG KCP Ranotana has been implemented very well but there are still indications of a decrease in collectability which may result in credit losses so that banks must manage credit losses by establishing CKPN.